Neotype designation for Cunaxa setirostris (Hermann, 1804) (Acari: Prostigmata: Cunaxidae) - Heyer, Jacob Den; Sergeyenko, Alexey L. (Zootaxa, 2009)
A neotype is designated for Cunaxa setirostris (Hermann, 1804). A full motivation, description and drawings of both sexes are provided.